Are Spanish companies involved in profit shifting? Consequences in terms of tax revenues - Ángela Castillo Murciego; Julio López-Laborda (Economics: The Open-Access, Open-Assessment E-Journal, 2017)
In this paper the authors analyze the existence of profit shifting between Spain and other OECD and EU countries. Using a sample of 1,169 Spanish subsidiaries owned by foreign OECD and EU parent companies and a sample of 317 EU subsidiaries owned by Spanish parent companies, taken from the AMADEUS Database for the period 2005 to 2014, and a simple tax rate difference as a measure of the tax incentive, the authors obtain a negative effect of corporate income taxes on reported profits. When the tax rate differences between Spain and the foreign countries vary by one percentage point, reported profits vary by approximately 2.7 to 3%. This is consistent with profit shifting activity by corporations and matches the empirical results in the literature. Furthermore, the authors calculate the impact of this activity on Spain's tax revenues from the sample of Spanish subsidiary companies. They obtain that the tax revenues vary from year to year, depending on the level of taxation of the main investor countries in Spain in comparison to the Spanish tax rate.
http://dx.doi.org/10.7910/DVN/K2KDZU
Keywords: F23; F69; H25; H26; H32; 330; profit shifting; multinational corporations; tax revenues; Spain